Try,
(%i1) eq10: w1-w2=-a*(p-d-m)^2 + a*(p-m)^2;
2 2
(out1) w1 - w2 = a (p - m) - a (p - m - d)
(%i2) eq11: w3-w1=-s*(p+d-m)^2 + s*(p-m)^2;
2 2
(out2) w3 - w1 = (p - m) s - (p - m + d) s
(%i3) first(linsolve(eq10, a));
w2 - w1
(out3) a = - ------------------
2
2 d p - 2 d m - d
(%i4) subst(out3,eq10);
2 2
(p - m - d) (w2 - w1) (p - m) (w2 - w1)
(out4) w1 - w2 = ---------------------- - ------------------
2 2
2 d p - 2 d m - d 2 d p - 2 d m - d
(%i5) first(linsolve(eq11, s));
w3 - w1
(out5) s = - ------------------
2
2 d p - 2 d m + d
(%i6) subst(out5,eq11);
2 2
(p - m + d) (w3 - w1) (p - m) (w3 - w1)
(out6) w3 - w1 = ---------------------- - ------------------
2 2
2 d p - 2 d m + d 2 d p - 2 d m + d
(%i7)
Rich
From: Mein Linuxrechner Arbeit
Sent: Tuesday, July 13, 2010 4:33 AM
To: maxima at math.utexas.edu
Subject: What is wrong?
Hello,
I tried to replase a in eq11 by the expression on the right side of "=". [a=-(w2-w1)/(2*d*p-2*d*m-d^2)]
Bit instead of doing that, s is simply replaced by a.
How can I make maxima do what I want?
Thanks in advance
(%i1) eq10: w1-w2=-a*(p-d-m)^2 + a*(p-m)^2;
(%i2) eq11: w3-w1=-s*(p+d-m)^2 + s*(p-m)^2;
(%i3) linsolve(eq10,[a]);
(%i4) eq11: subst(a,s,eq11);
--------------------------------------------------------------------------------
_______________________________________________
Maxima mailing list
Maxima at math.utexas.edu
http://www.math.utexas.edu/mailman/listinfo/maxima